2013
DOI: 10.1002/jcla.21608
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of HPLC Assay for Early Detection of Microalbuminuria in Chronic Kidney Disease

Abstract: These results suggest that ACR measurements by HPLC assay are better than TIA for early detection and monitoring of microalbuminuria in patients with diabetes and hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…From a clinical point of view, it has been suggested that elevated UAE, determined by HPLC, can precede the development of microalbuminuria measured by conventional methods (IRAE), and therefore it could be used for early detection [18,37]. Moreover, some studies have suggested that it could help identify more people at risk of death or CV disease than conventional methods [33,38].…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical point of view, it has been suggested that elevated UAE, determined by HPLC, can precede the development of microalbuminuria measured by conventional methods (IRAE), and therefore it could be used for early detection [18,37]. Moreover, some studies have suggested that it could help identify more people at risk of death or CV disease than conventional methods [33,38].…”
Section: Discussionmentioning
confidence: 99%
“…19), which shows that it has the highest sensitivity because of being strongest catalytic amplification, so it was selected to measure mAlb. Compared with the reported mAlb analysis method (Table S3), [31][32][33][34][35][37][38][39] this method is highly sensitive and easy to operate, and it is one of the best methods for detecting mAlb.…”
Section: Working Curvementioning
confidence: 99%
“…30 radioimmunoassay, 32 ELISA, 33 turbidity analysis, 34 highperformance liquid chromatography, and so on. 35 In this paper, a new gold nanoplasmon molecular spectral platform was established for rapid and selective quantitative detection of trace mAlb based on the immunoreaction-regulation of the GONR catalytic AuNP reaction.…”
Section: Introductionmentioning
confidence: 99%
“…This sensitive method to measure urinary protein will be useful for the screening of microalbuminuria because proteinuria in early stages of kidney diseases mostly consist of albumin. A high-performance liquid chromatography (HPLC) assay, which we reported as a sensitive method to detect microalbuminuria 4) , is also available but costs the same amount as TIA. The erythrosin B method has a 70% cost savings compared with TIA 3) .…”
Section: New Biomarkers Using Urine and Serum Samplesmentioning
confidence: 99%